Innovation (IntechOpen, 2024)
Investments in research and development are crucial for the innovation process in modern societies. There are more perspectives through which innovation can realize important results, including the knowledge creation source, the digital innovation relative to artificial intelligence (AI), the sustainable transition from traditional technology to renewable technology, and the role of the concept of entrepreneurship linked to innovation. Economic operators need different skills to cope with high degrees of competitiveness and achieve the highest profit levels. The analysis carried out in this book considers the interactions among innovation, sustainability, and entrepreneurship. This in-depth investigation identifies the relevant forces useful for the transformations of modern economies and suggests appropriate support policies.